Conservation status of the freshwater pearl mussel Margaritifera margaritifera in Portugal - Sousa, Ronaldo Gomes (2015)
Based on new information, the current conservation status of the freshwater pearl mussel Margaritifera margaritifera (Linnaeus, 1758) in Portugal is revised. Between 2010 and 2013 surveys were conducted in eight different rivers to assess distribution, abundance, size-frequency and preferential habitat of this species.Rivers Neiva, Cávado and Terva presented very low abundances (in the Cávado no specimens were found) and showed acute signs of ageing, calling into question the future survival of these populations. Although abundances were low in Rivers Bec¸ a, Paiva and Mente, juveniles were present and populations may improve their conservation status in the future, if appropriate management measures are applied. Rivers Rabac¸ al and Tuela presented the highest abundances of adults and juveniles and these two rivers have the highest potential for the conservation of freshwater pearl mussels in Portugal. However, these two populations have suffered severe declines in several stretches due to the construction of dams in recent years. Given that the Portuguese pearl mussel populations are at the southern range of the species distribution, their conservation should be a priority. This current description of the conservation status of M. margaritifera in Portugal can be used as a reference, and guide future research and management initiatives to better conserve this species.